TURKEY'S TRADITIONAL MIDDLE EAST POLICY AND OZALIST DIPLOMACY: GULF CRISIS REVISITED - Şaban Çalış (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
This essay is primarily designed to make an humble contri-bution to a theoretical debate concerning the conventional patterns of modern Turkish foreign policy in general, Turkey's Middle Eastern politics in particular and the role of leadership in decision making process vvithin the context of the Second Gulf Crisis and Özalist Diplomacy.